2011
DOI: 10.1111/j.1744-7402.2011.02617.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Monolithic YSZ Porous and Dense Layers through Multiple Slip Casting for Ceramic Fuel Cell Applications

Abstract: In this research YSZ porous support and thin dense functional electrolyte layers are fabricated via a slip‐casting method for fuel cell applications. The results show that calcination of YSZ starting powder is a crucial step in developing an effective porous structure having an interconnected void network for fuel cell applications. It is found that due to high surface area and high sinterability, as‐received Tosoh YSZ powder is not a suitable candidate for production of interconnected porous structures even w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…These observations were consistent with previous reports showing the importance of YSZ calcination on fabrication of porous supports [18,19].…”
Section: Methodssupporting
confidence: 94%
“…These observations were consistent with previous reports showing the importance of YSZ calcination on fabrication of porous supports [18,19].…”
Section: Methodssupporting
confidence: 94%
“…26,27 The effectiveness of using this processed YSZ powder in improving the electrochemical performance of LSM 28 and LSBT (La 0.4 Sr 0.5 Ba 0.1 TiO 3 ) 29,30 infiltrated cells has been shown recently. In addition, Batista and Muccillo 31,32 found that addition of a small amount of NiO to 8YSZ improves the sinterability of the electrolyte without affecting its overall conductivity.…”
Section: Resultsmentioning
confidence: 98%
“…Infiltration of porous YSZ substrates with anode or cathode materials can provide electrodes with superior electrochemical performance compared with traditionally prepared electrodes [75]. The authors developed different types of porous YSZ microstructures for infiltration by calcination of Tosoh YSZ (a commonly used YSZ powder for SOFC fabrication) at 1300 • C-1500 • C and milling the coarsened powder in an aqueous suspension for 72 h [76][77][78][79][80]. Calcination is an essential method for development of a porous substrate since asreceived YSZ powder normally has fine particles (250 nm), a high surface area (12-13 m 2 g −1 ) and thus high sinterability.…”
Section: Calcination and Milling Of Yszmentioning
confidence: 99%
“…Calcination and subsequent milling lead to the formation of particles with larger size (500-750 nm) and a lower surface area (3-5 m 2 g −1 ). The particle size correlates with the calcination temperature (figure 6) [79]. The reduced surface area of YSZ leads to generation of a porous structure following sintering at 1350 • C-1400 • C which contains interconnected pores (∼20%-25%) even without incorporation of any pore-formers.…”
Section: Calcination and Milling Of Yszmentioning
confidence: 99%